2021
DOI: 10.3389/fmicb.2021.631426
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Salmonella Typhimurium Invasion and Intracellular Survival Using Pyrogallol

Abstract: Salmonella enterica serovar Typhimurium, an intracellular pathogen, evades the host immune response mechanisms to cause gastroenteritis in animals and humans. After invading the host cells, the bacteria proliferate in Salmonella-containing vacuole (SCV) and escapes from antimicrobial therapy. Moreover, Salmonella Typhimurium develops resistance to various antimicrobials including, fluoroquinolones. Treating intracellular bacteria and combating drug resistance is essential to limit the infection rate. One way o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 74 publications
(94 reference statements)
0
11
0
Order By: Relevance
“…The annual cost of salmonellosis in poultry is estimated at approximately $11.6 billion in the United States ( Wernicki et al, 2017 ) and exceeds €3 billion in the European Union ( Ehuwa et al., 2021 ). Although antibiotic treatment is the first choice for Salmonella infection, the ability to proliferate in Salmonella -containing vacuole supports Salmonellae to escape from antimicrobial and phagocytic activities, then developing resistance ( Tierrez and García-del Portillo, 2005 ; Birhanu et al, 2021 ). Among several control tools, vaccines are valuable in decreasing the Salmonella incidence and shedding while simultaneously reducing the application of antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…The annual cost of salmonellosis in poultry is estimated at approximately $11.6 billion in the United States ( Wernicki et al, 2017 ) and exceeds €3 billion in the European Union ( Ehuwa et al., 2021 ). Although antibiotic treatment is the first choice for Salmonella infection, the ability to proliferate in Salmonella -containing vacuole supports Salmonellae to escape from antimicrobial and phagocytic activities, then developing resistance ( Tierrez and García-del Portillo, 2005 ; Birhanu et al, 2021 ). Among several control tools, vaccines are valuable in decreasing the Salmonella incidence and shedding while simultaneously reducing the application of antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports showed that daidzein inhibits the expression of caspases 3 and 9 in viral infections in vitro [ 69 ], while pyrogallol inhibits bacterial infections in vivo [ 70 ]. In addition, a decreased release of LDH and a decreased expression of IL-1β were observed in bacterial infections, suggesting that these compounds prevent an increase in the oxidative stress produced by infections [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…PG has previously been found to have an antibacterial effect against Salmonella enterica serovar Typhimurium ( 22 ), Acinetobacter baumannii ( 23 ), Pseudomonas pyocyanea , Pseudomonas putida , and Corynebacterium xerosis ( 24 ). PG showed synergistic activity with norfloxacin and gentamicin against Staphylococcus aureus ( 25 ), but the mechanism of action is unclear.…”
Section: Discussionmentioning
confidence: 99%